Cohydrothermal carbonization of cellulose and organic matter from municipal sewage sludge for the controllable synthesis of N-doped porous carbon for supercapacitor electrodes - Linxin Yin; Chang Liu; Yulu Yang; Zihan Du; Guanzhong Mu; Zeming Zhao; Changqing Cao; Pei-Gao Duan; Krzysztof Kapusta (Journal of Environmental Management, 2026)

Using degrading endophytic bacteria to detoxify the phthalic acid esters in crops from contaminated soil - Xiangyu Liu; Xiangrui Du; Xiangzhi Zuo; Zeming Wang; Bozena Czech; Patryk Oleszczuk; Yanzheng Gao (Journal of Environmental Sciences, 2025)

China’s practice from coastline management towards sea-land integration - Qiwei Zhao; Xin Teng; Xue Meng; Zeming Du; Panpan Zhang; Wanchao Kang (Frontiers in Marine Science, 2025)
Integrated Sea-land management is an important feature of ecosystem-based management, and it is also the trend of marine spatial planning. China is one of the first countries worldwide to implement marine spatial planning which is mainly expressed as marine functional zoning (MFZ), and it has established a coastline management system for the connection between marine management and land management. In this paper, 18 national and local coastline management policies in China are analyzed. It is concluded that coastline management ensures the formulation, implementation, evaluation, and revision of MFZ, promotes the extension of MFZ to land, gradually evolves into coastal zone planning based on coordinated land and marine development, and promotes sea-land integration management in China. Taking Tangshan City in Hebei Province as an example, it is further proven that at the local level, coastline management accelerates the progress of sea-land integration.

Methods and mechanisms for enhancing the water retention properties of Jiuzhaigou disintegrated rubble soils - Zeming Wei; Hongchao Xi; Xiangjun Pei; Xiaochao Zhang; Mao Qiu; Tiao Huang; Zhaocheng Wang; Junlian Jiang; Jie Du; Daijun Jian (Journal of Mountain Science, 2025)

The crustal structure of southeast Tibet from joint inversion of surface wave dispersion and gravity anomaly data - Haopeng Chen; Ruirui Fan; Nanqiao Du; Feng Bao; Zeming Zhang; Xuelei Li; Fang Zou; Chuang Xu (Journal of Asian Earth Sciences, 2024)

Relative reinforcing effects of dibutylone, ethylone, and N-ethylpentylone: self-administration and behavioral economics analysis in rats - Miaojun Lai; Dan Fu; Zeming Xu; Han Du; Huifen Liu; Youmei Wang; Peng Xu; Wenhua Zhou (Psychopharmacology, 2022)

Impact of meteorological conditions at multiple scales on ozone concentration in the Yangtze River Delta - Zezheng Zhao; Zeming Zhou; Ana Russo; Huadong Du; Jie Xiang; Jiping Zhang; Chengjun Zhou (Environmental Science and Pollution Research, 2021)